Designing ethical souvenirs to sustain the cultural integrity of Dunhuang heritage - Qiuxia Zhu; Rizal Rahman (PLoS ONE, 2025)
Mass-produced tourism souvenirs often dilute the cultural integrity of heritage sites, yet the mechanisms by which design philosophy and ethics sustain authenticity remain underexplored. This study investigates how designers’ philosophical stances and ethical practices shape authentic Dunhuang souvenirs. Adopting a qualitative single-case design, the investigation used purposive sampling to recruit 11 participants (eight designers and three cultural experts). Data from in-depth semi-structured interviews, non-participant observations, and document review were analysed via reflexive thematic analysis conducted concurrently with data collection. Three interlinked themes emerged: (1) design principles and philosophy, (2) ethical considerations, and (3) design implementation, coalescing into the Ethical Design for Cultural Integrity (EDCI) framework. The EDCI explains how authenticity and market relevance can be co-achieved by coupling value-laden design reasoning with procedural safeguards in production. Practical guidance includes: pre-brief checklists identifying non-negotiable cultural elements; embedded ethics procedures across decision points; and feedback-rich implementation cycles that preserve core motifs while meeting manufacturability and price envelopes. The study’s originality lies in integrating philosophy, ethics, and implementation into a single process view of heritage product design and in operationalising ethics as procedural governance rather than declarative intent, offering a replicable pathway for culturally responsible souvenir development.